Using Smartphones to Collect Quantitative Data on Lower Limb Functionality in People Who Have Suffered a Stroke. - Merchán-Baeza, Jose Antonio; González-Sánchez, Manuel; Cuesta-Vargas, Antonio (Elsevier, 2018)
Goal: The main objective was to use the inertial sensor integrated into a smartphone to collect quantitative data on lower limb functioning during execution of the timed up and go test and sit to stand test by people in the acute stage of stroke. The secondary objective was to analyze whether smartphones provide reliable quantitative data on performance of these functional tests. Material and methods: Cross-sectional analytical study involving 8 elderly people (M age = 67.50 years). Both tests were performed to parametrize and analyze the functionality, balance, and strength of lower limbs using an inbuilt inertial sensor of the smartphone. Time, difference in trunk position, angular displacement, angular velocity, and angular acceleration were measured and calculated for each stage at which both functional tests were divided. Results: The obtained results highlight the similarity in the angular displacement during the 2 stages into which the sitting-standing (flexion: 38.85° and extension: 38.10°) and the standing-sitting (flexion: 36.42° and extension: 36.45°) phases were divided. Mean velocities of .59 m/s and .61 m/s were registered during outward and return walking phases. The intra- and interobserver reliability of variables recorded with the inbuilt inertial sensor ranged from .860 to .897. Conclusions: Balance and muscle strength problems of stroke patients gave rise to the use of compensatory mechanisms when getting up from or sitting down in a chair and resulted in a reduction in walking speed that is sufficient to make walking in community contexts difficult. Smartphones has excellent reliability when used to quantify lower limb functioning in stroke patients.
https://openpolicyfinder.jisc.ac.uk/id/publication/4791
Keywords: Kinesiología; Fisioterapia; Enfermos cerebrovasculares - Rehabilitación; Kinematic; Balance; Clinimetric; Functional task; Stroke survivors